2021
DOI: 10.1177/23259671211033584
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction With Concomitant Meniscal Repair: Is Graft Choice Predictive of Meniscal Repair Success?

Abstract: Background: When meniscal repair is performed during anterior cruciate ligament (ACL) reconstruction (ACLR), the effect of ACL graft type on meniscal repair outcomes is unclear. Hypothesis: The authors hypothesized that meniscal repairs would fail at the lowest rate when concomitant ACLR was performed with bone--patellar tendon--bone (BTB) autograft. Study Design: Cohort study; Level of evidence, 3. Methods: Patients who underwent meniscal repair at primary ACLR were identified from a longitudinal, prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
(81 reference statements)
1
6
0
Order By: Relevance
“…Several biomechanical studies have reported that the load of the medial and lateral menisci increases in the ACLdeficient knee, and secondary meniscus lesions in the ACLdeficient knee can result from this increased load on the menisci due to increased anterior tibial translation. [37][38][39] Moreover, it has been reported that there is a significant increase in meniscal injuries after ACL rupture before the incidence of cartilage lesions rises; this corroborates previous reports stating that the integrity of the meniscus is important for preventing early degeneration of the articular cartilage. 40 Therefore, the IKDC and Lysholm scores of the study group were superior to those of the control group after the operation; our analysis was based on the stability of the joint being restored after meniscus suture and healing, and the damage to the cartilage was reduced.…”
Section: Discussionsupporting
confidence: 86%
“…Several biomechanical studies have reported that the load of the medial and lateral menisci increases in the ACLdeficient knee, and secondary meniscus lesions in the ACLdeficient knee can result from this increased load on the menisci due to increased anterior tibial translation. [37][38][39] Moreover, it has been reported that there is a significant increase in meniscal injuries after ACL rupture before the incidence of cartilage lesions rises; this corroborates previous reports stating that the integrity of the meniscus is important for preventing early degeneration of the articular cartilage. 40 Therefore, the IKDC and Lysholm scores of the study group were superior to those of the control group after the operation; our analysis was based on the stability of the joint being restored after meniscus suture and healing, and the damage to the cartilage was reduced.…”
Section: Discussionsupporting
confidence: 86%
“…Patients included in this review received different ACL grafts, thereby introducing possible bias. Salem et al report different failure rates of meniscal repair with concomitant ACLR for different types of ACL grafts [ 29 ]. To further identify the influence of the meniscal tear zone on the actual healing of meniscal tears, a large-scale study should be conducted in a more homogenous patient group with a considerable number of tears in all meniscal vascular regions.…”
Section: Discussionmentioning
confidence: 99%
“…The elected surgical technique for ACLR appears to influence return to the pre-injury level of sport outcomes. Certain surgical factors, including graft choice for ACLR [42], augmentation of the ACLR to include a lateral extra-articular procedure (LEAP) [43], and concomitant meniscal repair/ligamentous reconstruction at the time of ACLR have all been observed to impact outcomes related to an athlete's return to their pre-injury level of sport [44]. Of these factors, graft selection appears particularly important, because higher RTS rates have been observed after ACLR with a BPTB autograft than with HT autografts or an all-soft tissue allograft [10,42,45].…”
Section: Aclr Technique and Rtsmentioning
confidence: 99%
“…Compared to an isolated ACLR, meniscal repair and/or other knee ligament reconstructions at the time of ACLR are known to reduce RTS rates [15,44,45,54], and the number of reconstructed ligaments (i. e., 2 or more ligaments reconstructed at the time of ACLR) appears to influence RTS rates more than if the meniscus was intact versus repaired or resected [45,54,55]. A cohort study by Bakshi et al [55] reported that 43.5 % of National Football League players were able to return to their pre-injury level of sport the next season after an ACL + medial collateral ligament (MCL) injury/surgery compared to only 18.5 % after an ACL, posterior cruciate ligament, and fibular collateral ligament injury/surgery.…”
Section: Aclr Technique and Rtsmentioning
confidence: 99%
See 1 more Smart Citation